Governing mobile Virtual Network Operators in developing countries. (February 2019) - Son, Pham Hai; Son, Le Hoang; Jha, Sudan; Kumar, Raghvendra; Chatterjee, Jyotir Moy
Abstract: Telecommunication is described by enormous settled, sunk, and irreversible speculation, which makes it high-hazard undertaking. The circumstance is additionally aggravated in the mobile part by progressive ages of innovation. The introduction of Mobile Virtual Network Operators (MVNOs) added value for both operators and customers; for the operators by using their available excess capacity and for the customers by offering innovative and several niche value-added services that were not offered by Mobile Network Operators (MNOs). However, mobile operators in developing nations are urban and semi-urban based, and very few operators provide services in rural areas. There are many un-served and under-served market segments still available. The major issue for developing nations is the formulation and implementation of policies, rules, and regulations. With an extensive variety of brands, companies are willing to enter the mobile business. An exclusively exploited radio access network by mobile network operators, new concepts and strategies are required to bring the opportunity for both telecom and non-telecom organizations to take part in the mobile sector. In this paper, we aim to develop a regulatory framework for MVNO in developing nations' telecommunication market as follows: first, to carry out a thorough analysis of market and draft a feasibility study for MVNOs in the telecommunications ("telecom") market in developing nations; and second, to develop required regulations for enhanced growth opportunities in the telecom market. This can be regarded as the effort for creating infrastructure for deploying e-Government in the developing countries. Highlights: We examined deployment of Mobile Virtual Network Operator in developing nations. A new regulatory framework and guidelines for MVNO were proposed. We analyzed the best global practices on MVNO. MVNO was discussed in Telecom Market where international practices are zero level. It is a reference document for the government to put the sector into priority.